STUDENTS LANGUAGE ONLINE LEARNING METHODS EFFECTIVE BENEFIT SKILLS DEVELOP - Khamrаyeva Shahlo Shuhratovna (International Journal of Literature and Language Studies, 2026)
Current science has developed one in time information The technologies are also noticeable . developed it is going from there of no use possible no.Modern approaches language study in the field as well the impact directly shows that even they through language study for a long time is getting better if we say right This will be in the article students language study​ abilities to develop directed online training their training organization to grow methodology studied . In the article language in learning online from platforms of use advantages open given .